Nerve Targeting via Myelin Protein Zero and the Impact of Dimerization on Binding Affinity - Berehova, Nataliia; Buckle, Tessa; van Meerbeek, Maarten P.; Bunschoten, Anton; Velders, Aldrik H.; van Leeuwen, Fijs W. B. (Molecules, 2022)
Background: Surgically induced nerve damage is a common but debilitating side effect. By developing tracers that specifically target the most abundant protein in peripheral myelin, namely myelin protein zero (P0), we intend to support fluorescence-guided nerve-sparing surgery. To that end, we aimed to develop a dimeric tracer that shows a superior affinity for P0. Methods: Following truncation of homotypic P0 protein-based peptide sequences and fluorescence labeling, the lead compound Cy5-P0101–125 was selected. Using a bifunctional fluorescent dye, the dimeric Cy5-(P0101–125)2 was created. Assessment of the performance of the mono- and bi-labeled compounds was based on (photo)physical evaluation. This was followed by in vitro assessment in P0 expressing Schwannoma cell cultures by means of fluorescence confocal imaging (specificity, location of binding) and flow cytometry (binding affinity; KD). Results: Dimerization resulted in a 1.5-fold increase in affinity compared to the mono-labeled counterpart (70.3 +/− 10.0 nM vs. 104.9 +/− 16.7 nM; p = 0.003) which resulted in a 4-fold increase in staining efficiency in P0 expressing Schwannoma cells. Presence of two targeting vectors also improves a pharmacokinetics of labeled compounds by lowering serum binding and optical stability by preventing dye stacking. Conclusions: Dimerization of the nerve-targeting peptide P0101–125 proves a valid strategy to improve P0 targeting.